A project on “wine and distillation trade” course. The consumers mindset regarding retsina - Iliadou, Georgia; Giannopoulos, Dionisis; Nikolakakis, Konstantinos (International Conference on Business and Economics - Hellenic Open University, 2023)
On early ‘70s the consumers stopped preferring retsina, due to many reasons, some of them have already been mentioned, like the bad quality of the wine, that the owners of small Greek restaurants used and with the use of resin they were trying to cover the wine’s flaws, of the change of the lifestyle, because anything that was related to the tradition or the countryside was characterized as outdated. Finally, the living standards change and that made the consumers seek of more elegant and aromatic and wines. The last decade despite all the above facts, some wine producers have started to produce higher quality of resinated wine to ensure that this product will remain on the market. The cause of this research is to figure out what is today’s consumers mindset regarding resonated wine and their opinion on the new trend of higher quality retsina. The method which used, was to collect data through a questionnaire. The questions are about demographics, questions about wine consumption and questions about retsina. The questionnaire was shared through Social Media. The number of answers reached 768 questionnaires throughout Greece. The results were processed with SPSS Statistics 22. Keywords: marketing, resinated, wine, Retsina, SPSS analysis JEL Classification Code: M31, L36